Стилістичний потенціал звуконаслідувальних слів у сучасній українській мові (на прикладі новелістики 60-х років XX ст.) - Мішеніна, Тетяна; Mishenina, Тetiana (Східноєвропейський національний університет імені Лесі Українки, 2014)
На основі аналізу стилістично-функціональних особливостей звуконаслідувальних слів виокремлено чотири класи уживаних у сучасній українській мові звуконаслідувальних комплексів, що реалізують стилістичний потенціал. З’ясовано, що задля досягнення звукового ефекту використовуються одно- і багатокомпонентні утворення, авторські асоціативні звукові компоненти. Interjections and sound systems traditionally considered accepted in one group, but the structure and semantics of audio components are more close relationship with the meaning of the word. Onomatopoeic words expressing general ideas, have a constant sound structure and the structure, which is understood by all carriers of a particular language, form a basis to create new words, should be the object of study. On an example novelistic 60 s. ХХ century was discovered stylistic potential of such groups onomatopoeic words: onomatopoeia, which are associated with the man and his actions: transmission features of laughter; transmission features a whistle; transfer of physical condition; transmission emotional state; onomatopoeia associated with handling human to nature; onomatopoeia related to actions with everyday objects; onomatopoeia, transmitting the sound effect of human actions; onomatopoeia votes birds; onomatopoeia of the sounds produced by insects; onomatopoeia animal noises (wolf, hedgehog, goat); onomatopoeia arachnids (to a certain extent associative sound association). Found a powerful stylistic potential onomatopoeia transmitting sound effects sound effects due to work with tools: sound effect from the fall; sound effect from eating animals; sound effect of the environment, natural phenomenon; mimicry mechanisms. Performing stylistic function onomatopoeic word origin or corresponding onomatopoeia, I model the words in some cases to some extent can lose modeling sounds character, ceasing to be a proper onomatopoeia: the sounds of speech, their generators, to a certain extent acquire functions that distinguish meanings. In this case, the modeling function, in turn, weakens. As a result, lost the ability to imitative pronunciation (can also be lost variability sound composition – change or drop certain sounds, syllables, etc.). For the modern Ukrainian language is characterized by the use of words to express homonymous of human activities, which reflect sound animate and inanimate nature. Sound systems create sounds capes, as well as contribute to the effect of polyphony in artistic speech.
Stylistic Potential of Onomatopoeic Words in Modern Ukrainian Language (for Example Novelistic 60 s. ХХ century).
Keywords: вигуки; звуконаслідувальні слова; стилістично-функціональні особливості; стилістичний потенціал; структурно-семантичні особливості мовної одиниці; звуконаслідувальні утворення; interjections; sound systems; stylistic and functional features; stylistic potential; structural and semantic features of the language unit; sound education